2021
DOI: 10.1152/ajpcell.00167.2021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of variants of ISL1 gene promoter and cellular functions in isolated ventricular septal defects

Abstract: Ventricular septal defects (VSD) are the most common congenital heart defects (CHD). Studies have documented that ISL1 has a crucial impact on cardiac growth, but the role of variants in the ISL1 gene promoter in patients with VSD has not been explored. In 400 subjects (200 isolated and sporadic VSD patients: 200 healthy controls), we investigated the ISL1 gene promoter variant and performed cellular functional experiments by using the dual-luciferase reporter assay to verify the impact on gene expression. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The promoter is a component of a gene that controls the onset and extent of gene expression, playing a key role in transcriptional regulation. Recently, studies have demonstrated that variants within the promoter region of a gene may be correlated to changes in gene expression levels, leading to disease (de Vooght et al, 2009; Juge et al, 2018; Zheng et al, 2021a; Zheng et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…The promoter is a component of a gene that controls the onset and extent of gene expression, playing a key role in transcriptional regulation. Recently, studies have demonstrated that variants within the promoter region of a gene may be correlated to changes in gene expression levels, leading to disease (de Vooght et al, 2009; Juge et al, 2018; Zheng et al, 2021a; Zheng et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that genetic polymorphisms in MYH6 are associated with risk of VSD [ 17 , 18 , 30 ]. Further, there is growing evidence that variants in the gene promoter play a key role in cardiac transcriptional regulation [ 19 21 , 31 , 32 ]. Based on the STRING database and a previous study [ 33 ], we found that the major proteins interacting with MYH6 protein are basically involved in myocardial development.…”
Section: Discussionmentioning
confidence: 99%
“…As we have reported [ 19 , 20 ], genomic DNA was extracted from the peripheral blood of each subject using a blood genomic DNA extraction kit. Primers were designed according to the CITED2 reference sequence (NCBI: NG_016169.1).…”
Section: Methodsmentioning
confidence: 99%